Do External Auditors Perform a Corporate Governance Role in Emerging Markets? Evidence from East Asia - FAN, JOSEPH P. H.; WONG, T. J. (Journal of Accounting Research, 2005)
ABSTRACT In emerging markets, the agency conflicts between controlling owners and the minority shareholders are difficult to mitigate through conventional corporate control mechanisms such as boards of directors and takeovers. We examine whether external independent auditors are employed as monitors or as bonding mechanisms, or both, to alleviate the agency problems. Using a broad sample from eight East Asian economies, we document that firms with agency problems embedded in the ownership structures are more likely to employ Big 5 auditors. This relation is evident among firms that raise equity capital frequently. Consistently, firms hiring Big 5 auditors receive smaller share price discounts associated with the agency conflicts. Also, we find that Big 5 auditors take into consideration their clients' agency problems when making audit fee and audit report decisions. Taken together, these results suggest that Big 5 auditors do have a corporate governance role in emerging markets.